Circulating pattern and genomic characteristics of influenza B viruses in Taiwan from 2003 to 2014 - Kuo, Shu-Ming; Chen, Guang-Wu; Velu, Arul Balaji; Dash, Srinivas; Han, Yi-Ju; Tsao, Kuo-Chien; Shih, Shin-Ru (Journal of the Formosan Medical Association, 2016)
Influenza B viruses are antigenically classified into Yamagata and Victoria lineages according to their hemagglutinin (HA) proteins. These two lineages are known to either appear sequentially or cocirculate in Taiwan. Taiwanese influenza B viral HA and neuraminidase (NA) sequences between 2003 and 2014 were determined and analyzed. A time-scaled phylogenetic tree was constructed to decipher the evolutionary trends of these sequences, and the reassortment between the two lineages. Positively selected amino acids were predicted, demonstrating the adaptive mutations of the circulating pattern. The HA phylogenetic tree revealed that the Victoria lineage evolved into a ladder-like pattern, whereas the Yamagata lineage exhibited complex topology with several independently evolved clades on which viruses from different influenza seasons interlaced. For several seasons, HA sequences were found to be dominated by strains of the same lineage as the corresponding vaccine strain. Inspecting these sequences revealed that frequent mutations occurred in neutralizing epitopes and glycosylation sites. Amino acid positions 212 and 214 of N-glycosylation sites, which are known to be critical determinants of receptor-binding specificity, were found to be subject to positive selection. No drug-resistant sites were noticed in the NA sequences. In addition, we identified several cases of NA reassortment with an overall incidence rate of 6% for the investigated Taiwan strains. We highlighted the interplay between mutations in the glycosylation sites and epitope during HA evolution. These are crucial molecular signatures to be monitored for influenza B epidemics in the future.